Extension of Honey and Organic Fertilizer as Products of Animal Origin on Elementary School Students in Nagari Saniangbaka, X Koto Singkarak, Regency of Solok, West Sumatra - Putra, Aronal Arief; Azzuhri, Alya Putri; Sari, Putri Amalia; Aulia, Renasya Nurul (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Community engagement was conducted to introduce food and non-food products of animal origin to elementary school students in Nagari Saniangbaka. Honey was selected as a food of animal origin, while organic fertilizer was selected as a non-food of animal origin. The former extension was conducted in SDN 08 Saniangbaka, while the latter extension was conducted in SDN 10 Saniangbaka. The goal of these activities was to introduce honey and animal fertilizer in order to improve their basic science knowledge and enhance health and environmental awareness. The activities were conducted through short lectures, discussions, quizzes, and the distribution of reward food. Extension of honey began with an introduction to bees as honey-producing insects, types of honey-producing bees, sources of nectar-producing plants, the honey production process, and the health benefits of honey. Extension of organic fertilizer was explained regarding various types of livestock and poultry, the potential for manure to turn into pollution if not utilized, animal manure as a by-product that can be converted into fertilizer, and the role of fertilizer for plants. The first activity significantly broadens participants' insight regarding the important role of bees and honey for humans. The second activity positively increases the interest in utilizing animal by-products for plant growth and fosters environmental concern. Both activities enrich students' science insight toward selected products of animal origin, and improve their awareness of food and the environment.